The effectiveness of the in-house prehospital care training program for the emergency medical team - Nurumal, Mohd. Said; Jamaludin, Thandar Soe @ Sumaiyah; Mat Isa, Rif'atunnailah; Che Hasan, Muhammad Kamil; Abdul Hamid, Abdul Alif; Win, Kyu Kyu; Noviani, Wulan (Media Shed, 2024)
In the Malaysian context, the prehospital personnel are not only solely dedicated to the prehospital service but at the same time they are also functioning as hospital-based staff in the emergency and trauma department. Based on the previous study, the perceived level of knowledge and skills of prehospital care personnel at SASMEC @ IIUM is still not properly executed overall. Thus, this study aimed to assess the effectiveness of the prehospital care in-house training programme for the emergency medical team in SASMEC@IIUM. A total of 28 prehospital care personnel participated in this study. The prehospital care in-house training programme included both lectures and demonstration sessions. Then the participants answered a self-administered questionnaire that originated from the WHO's Essential Knowledge and Skills Questionnaire to test the effectiveness of the prehospital care in-house training programme. It was found that the knowledge and skills of the studied participants drastically increased after attending the programme. Besides, there were also positive associations found between the participants’ sociodemographic data, their knowledge and their skills related to prehospital care with a p-value of < 0.05. Therefore, this study's findings indicated a continuous and sustained structured in-house training programme for the emergency medical team in SASMEC@IIUM to provide quality care towards society.